Tempo de reação do jogador de goalball na interceptação/defesa do lançamento/ataque - Silva, Gilberto Carlos Pereira da (2008)
Goalball is a sport in group created to blind people and visual deficient. The game happens for the mobilization of hearing and tactile perceptions of players. This search has objective to analyze the behavior of movement of blind players and visual deficient of goalball both sex to value the influence the time of reaction in the efficiency of action of defense. The participant of search was nine blind athletic and visual deficient both sex that integrate the national team of goalball that participated of 3º Mundial Games of IBSA, realized in São Paulo, august 2007. The data were collected for the film to have image of actions of movement of persons in realization of actions of defense. The data was analyze and developed for the model biomechanical to base in anatomic points and segment of basic position of defense, this data were treated using the software specific of analyze of movement, DgeeMe Version 1.0b. To value the time of reaction and efficiency of subject of action of intercept/defense of launch/attack in the goalball modality, verified if time of reaction of subject was according of standard mentioned in literature. The repetition of movement and promptness to action are characteristic that influence a better answer of subjects in relation to task, facilitating a diminution the time of reaction. In relation to time of reaction among actions of subjects resulted in defense of ball and actions resulted in point, verified it doesn't have difference to time of reaction between both groups of actions.